Permainan tradisional sebagai media pembelajaran : dampaknya terhadap motivasi dan keterlibatan siswa - Tiyar Edwin Jahya; Taufik Hidayat; Sapto Wibowo (Physical Education Departement of University PGRI Jombang, 2025)
This study aims to analyze the effect of traditional games as a learning medium on students’ motivation and engagement in elementary schools. The research background was based on the low level of motivation and engagement when students participate in conventional learning activities. The study employed a one group pretest-posttest design with a sample of 27 elementary school students. Research instruments consisted of motivation and engagement questionnaires that had been tested for validity and reliability. Data were analyzed using the Shapiro-Wilk normality test and paired sample t-test. The results showed significant differences between pretest and posttest scores for both students’ motivation and engagement. The average score of motivation increased from 67.22 in the pretest to 79.26 in the posttest, while the engagement score rose from 64.96 in the pretest to 76.96 in the posttest. The paired sample t-test revealed a significance value of 0.000 (p < 0.05), indicating a significant improvement after the application of traditional games in learning. It can be concluded that traditional games as a learning medium are effective in enhancing students’ motivation and engagement. These findings highlight the importance of integrating traditional games into the learning process in elementary schools as a strategy to create enjoyable, contextual, and holistic learning experiences that support students’ overall development